FACTORS RELATED TO CHINESE CUSTOMERS’ ONLINE PURCHASE INTENTION: THE CASE STUDY OF JINGDONG.COM ONLINE SHOPPING’S CUSTOMER IN CHINA - Li Zhuo Zhen; Arti Pandey; Surachai Traiwanmakij; Komm Pechinthorn; Jirangrug Samarkjarn (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
In the past two decades, the development of China's Internet industry has been very rapid. Many service industries around the Internet have also been on the rise, of which, online shopping has become the fastest growing Internet industry chain. This study will focus on analyzing customer’s online purchase intentions, the researchers found four variables that have a relationship with customers online purchase intention. Primary data of this research were collected by online and offline questionnaires which were distributed to Chinese customers’ who has ever used JD.com service to found how JD.com service related to customers’ purchase intention. In this thesis, researchers collected 273 questionnaires to summarize the correlations among the independent variable and dependent variables. The results showed that all three independent variables which are perceived reputation, customer attitude and convenience variable are statistically significant and have positive relationship with customer’s online purchase intention.